MAQASID-AS-SHARIAH AND HUMANITARIAN PROVISIONS: ANALYSIS OF THE ACTIVITIES OF MULTI-PURPOSE WOMEN CENTRE KATSINA, KATSINA STATE - Abubakar Sani; Bilkisu Jibrin Gane (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2026)
Maqasid as-Shari'ah aims to promote the public interest and social welfare of the Muslim community by providing what is beneficial and protecting them from harm. This research examines the application of Maqasid as-Shari'ah in the humanitarian activities of the Multi-purpose Women Centre Katsina, and the role and impact of the Centre's poverty alleviation schemes on the socio-economic lives of the less privileged in society. Using extensive interviews and observations across various sections of society, the study found that these activities helped reduce poverty among the less privileged. The work further suggests that the Centre employ staff who are well acquainted with the field of Islamic welfare/humanitarianism to further enhance the Centre's humanitarian activities in line with Islamic ideals. There is also a need for project design transformation, including programming options with an Islamic, integrated, sustainable development model, and the creation of networks and partnerships, such as organizing lectures by experts on Islamic humanitarianism, to further boost and integrate the Centre's activities, with a stronger focus on the framework of Maqasid as-Shari'ah, which are the essential necessities of Islamic law towards enhancing brotherhood, peace, mutual love and a better harmonious society. This is its main contribution to existing knowledge.